The Effect of Tax-Favored Retirement Accounts on Capital Accumulation - İmrohoroğlu, Ayşe and İmrohoroğlu, Selahattin and Joines, Douglas H. (American Economic Review, 1998)
In this paper we develop an applied general equilibrium model to examine the effects of tax-favored retirement accounts on the capital stock. The results from our benchmark model indicate that a modest IRA contribution limit similar to that in effect during the early 1980's raises the steady-state capital stock by 6.18 percent; approximately 9 percent of IRA contributions constitutes incremental saving. Our results lend support to recent suggestions that retirement accounts with favorable tax treatment only for contributions above some base amount might provide more stimulus to saving than conventional IRAs.